SOME PECULIAR FEATURES IN SHRINKAGE OF CLAY MASS DURING DRYING PROCESS - I. K. Ivanovsky; S. N. Osipov; L. V. Rafeenkova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains results of correlation and stochastic analysis for regularities in shrinkage of the Lukoml clay and molding mass prepared on its base, and also the Gloukhov and Gloukhovetsky kaolin and their mixtures.It has been revealed that an exponent is the most convenient approximation form of the shrinkage characteristic for the Lukoml clay and molding mass prepared on its base within significant range of moisture changes.After products’ molding in a vacuum press a linear dependence is considered as the most convenient type of approximation within the range of moisture changes and with the main shrinkage.